2006
DOI: 10.1086/506518
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Populations and Mass Loss in M15: ASpitzer Space TelescopeDetection of Dust in the Intracluster Medium

Abstract: We present Spitzer Space Telescope IRAC and MIPS observations of the galactic globular cluster M15 (NGC 7078), one of the most metal-poor clusters with a [Fe/H] = -2.4. Our Spitzer images reveal a population of dusty red giants near the cluster center, a previously detected planetary nebula (PN) designated K648, and a possible detection of the intra-cluster medium (ICM) arising from mass loss episodes from the evolved stellar population. Our analysis suggests (9 ± 2) × 10 −4 M ⊙ of dust is present in the core … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
121
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(128 citation statements)
references
References 60 publications
(88 reference statements)
6
121
1
Order By: Relevance
“…There is a notable lack of detections of intracluster material with the Spitzer Space Telescope. Only two clusters of the many observed with Spitzer have "possible" detections of intracluster material (Boyer et al 2006;Barmby et al 2009). One suggestion for removal of intracluster material is ram-pressure stripping by the galactic halo (Frank & Gisler 1976, Okada et al 2007), but Spitzer observations cannot confirm the expected relation between cluster kinematics and the presence (or upper limit) of dust (Barmby et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is a notable lack of detections of intracluster material with the Spitzer Space Telescope. Only two clusters of the many observed with Spitzer have "possible" detections of intracluster material (Boyer et al 2006;Barmby et al 2009). One suggestion for removal of intracluster material is ram-pressure stripping by the galactic halo (Frank & Gisler 1976, Okada et al 2007), but Spitzer observations cannot confirm the expected relation between cluster kinematics and the presence (or upper limit) of dust (Barmby et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (1995) placed an upper limit of 0.4 M for the molecular gas in M15 from CO observations with the 15 m James Clerk Maxwell Telescope Durrell & Harris (1993). Dusty giants identified with the Spitzer Space Telescope (Boyer et al 2006) and observed with Hectochelle are denoted by squares. The redward "hook" seen among the brightest stars in M15 is not intrinsic to the stars but rather results from saturation of the photographic images (Sneden et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Absolute magnitudes are obtained by assuming (m − M) V = 15.37 (Harris 1996). on Mauna Kea. Using the Spitzer Space Telescope, Boyer et al (2006) detected a population of dusty red giants near the center of M15. Observations from Spitzer with the Multiband Imaging Photometer for Spitzer (MIPS) also revealed the ICM discovered by Evans et al (2003) near the core of the globular cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Other Spitzer-based studies available on 47 Tuc (Boyer et al 2010), ω Cen (Boyer et al 2008;McDonald et al 2009), M 15 (Boyer et al 2006), and NGC 362 ) find that mass loss is confined near the tip of the RGB, and occurs mostly in AGB or variable stars, with the exception of M 15 where a population of dusty red giants has been detected. These conclusions, however, were revised by Origlia et al (2010) in 47 Tuc where the use of a better dust indicator allowed them to detect dust at fainter magnitudes along the RGB.…”
Section: Introductionmentioning
confidence: 91%
“…Eight Galactic GCs were observed and again only upper limits were found, which is well below expectations for dust production from mass loss in cluster RGB and AGB stars (Barmby et al 2009, and references therein). The only exception is NGC 7078 (M 15) which shows high signal-to-noise evidence for an IR excess and hence dusty intracluster medium in the core (Evans et al 2003;Boyer et al 2006), and possibly ω Cen if the four dust clouds that were detected in the field are confirmed to be intracluster material that is in the process of escaping from the cluster (Boyer et al 2008). This implies that either dust production from mass loss is less efficient, or that the mechanisms able to remove the intracluster material are more efficient than commonly believed.…”
Section: Introductionmentioning
confidence: 99%